Shelf-Life Extension of Large Yellow Croaker (Larimichthys crocea) Using Active Coatings Containing Lemon Verbena (Lippa citriodora Kunth.) Essential Oil - Li, Bo; Wang, Xuesong; Gao, Xin; Ma, Xuan; Zhang, Leilei; Mei, Jun; Xie, Jing (Frontiers in Nutrition, 2021)
Active coating could improve the fish quality and extend the shelf life. This study investigates the effect of locust bean gum (LBG) and sodium alginate (SA) active coatings containing lemon verbena (Lippa citriodora Kunth.) essential oil (LVEO) emulsions on microbiological, physicochemical and organoleptic evaluation of large yellow croaker (Larimichthys crocea) samples during refrigerated storage at 4°C. Results showed that LBG-SA coatings incorporated with 0.30 or 0.60% LVEO emulsions significantly inhibited the growth of mesophile bacteria, Pseudomonas spp., H2S-producing bacteria, lactic acid bacteria (LAB) and psychrophilic bacteria, and reduce the productions of trimethylamine (TMA), total volatile basic nitrogen (TVB-N) and ATP-related compounds. Further, the LVEO treatments also retarded the water migration and maintained the organoleptic evaluation results of large yellow croaker during storage at 4°C. In conclusion, the LBG-SA active coatings incorporated with LVEO emulsions maintained the quality and extended the shelf life of large yellow croaker during refrigerated storage.